Efeitos do alfa-tocoferol nas lesões de isquemia-reperfusão induzidas em pata direita de ratos - Bitu-moreno, José; Gregório, Eliza Aparecida [UNESP]; Maffei, Francisco Humberto A. [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2001)
Studies indicate that oxygen-derived free radicals may play a major role in ischemia-reperfusion injury. Alpha-tocopherol acts in vivo as a free radical scavenger. Our purpose was to elucidate whether alpha-tocopherol could change the evolution of ischemia/reperfusion in the right hindlimb of rats. The animals were randomly allocated in the following groups: Group 1(G1)- control without ischemia. Groups 2 and 3(G2,3): four hours ischemia and two hours reperfusion. The animals of group 2 were treated with saline and those of the group 3, treated with alpha-tocopherol, 50 mg/Kg. Parameters were the foot volume and circumference, 99mTc-Pyrophosfate uptake in the soleus muscle, plasmatic creatine-phosphokinase (CPK), and transmition eletronic microscopy (TEM)of muscle cells. The foot volume and circumference of the animals of G2 were significantly greater than in G1. In the G3 these measurements did not differ from the G1. Pyrophosphate uptake and CPK measurements were increased in G2,G3 when compared to the animals of G1, but there were no differences between the ischemic groups. Cell injury, when examined by TEM, was less severe in two of three animals of G3, when compared to the G2. Conclusion: The treatment with alpha-tocopherol diminuished edema formation, but only partially protected muscle cells from injury.

Recentes estudos demonstraram que os radicais livres de oxigênio parecem desempenhar papel importante nas lesões de isquemia-reperfusão. O alfa-tocoferol(AT) age in vivo como um anti-oxidante. Nosso objetivo foi o de verificar se o AT atenuava as lesões de isquemia-reperfusão em pata direita de ratos. Os animais, randomizados, foram divididos nos seguintes grupos(G): G1-controle sem isquemia; G2 e G3 - quatro horas isquemia e duas reperfusão. Os animais do G2 foram tratados com salina e os do G3 com AT, 50mg/kg. Como parâmetros examinamos as alterações de volume e circunferência do pé direito ao longo do experimento, assim como a captação de 99mTc-pirofosfato e a microscopia eletrônica de transmissão do músculo soleus direito. Os aumentos de volume e circunferência do pé dos animais do G2 foram estatisticamente maiores quando comparados com o G1. As medidas do G3 não diferiram do G1. A captação de 99mTc-pirofosfato foi bem aumentada nos G2 e G3, quando comparados ao G1, porém sem diferenças entre os grupos isquêmicos. As lesões ao MET foram menos intensas em três animais do G3, quando comparados ao G2. Conclusão: O tratamento com AT diminuiu a formação do edema mas só protegeu parcialmente as células musculares contra as lesões de isquemia-reperfusão.
Effect of alpha-tocopherol on the ischemia/reperfusion lesions induced in the hindlimb of rats
Keywords: Alpha-tocopherol; Ischemia; Reperfusion; Rats; Alfa tocoferol; Isquemia; Reperfusão; Ratos